Analisis Penerapan Manajemen Risiko dalam Pelaksanaan Pembangunan Proyek Konstruksi Gedung High-Rise Building (RSIA) Stella Maris - Bagus, Muhammad; Kurniawan, Fredy (Portal: Jurnal Teknik Sipil, 2025)
In the implementation of construction projects, particularly high-rise building construction, PMBOK provides guidelines for project risk management, covering risk planning, identification, qualitative and quantitative analysis, response planning, response implementation, and risk monitoring. As the scale of a project increases, so does the potential for emerging risks. If these risks are not properly managed, they can impede project progress and cause material losses. The research method used is a survey with the distribution of questionnaires, aiming to identify risk factors and their impacts on stakeholders in the construction of the 10-story RSIA Stella Maris building in Medan. To classify the risks, the Severity Index method was applied based on respondent answers. This study aims to identify risks encountered during the construction phase of the building, analyze the assessment results of identified risks, and map out the responses taken to address these risks. The data analysis results show that there are 27 risk variables, including 4 force majeure risks, 5 design and technology-related risks, 3 contractual risks, 5 material and equipment risks, 3 labor risks, 3 managerial risks, and 9 environmental risks. Referring to the probability and impact values of the 21 identified risk variables, 11 risk categories are avoided (risk avoidance), 8 categories are transferred (risk transfer), and 1 category is reduced (risk reduction). The conclusion of the RSIA Stella Maris high-rise building project implementation shows that the application of risk management in accordance with ISO 31000-2018 has only reached 85%, as the project management and implementation teams have not fully implemented the risk management process.